PENINGKATAN MEMBACA SISWA MELALUI STRATEGI PEMBELAJARAN CTL DI SMA NEGERI 1 ANGKOLA BARAT TAHUN PELAJARAN 2025-2026 - Gultom, Fita Delia; Caniago, Elnila (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2025)
This research was conducted at SMA Negeri 1 Angkola Barat in the 2025-2026 academic year with a sample size of 33 students. From the research that has been done, the results obtained are that in the pre-cycle, 50% still reach the KKM. While in cycle 1, there are 25 students who still get scores above the KKM with a percentage of 75%. So the research was carried out again with the same actions in cycle 2, namely the number of students who have completed the KKM is 30 students with a percentage of 90%, so the research was stopped because it is in accordance with the target, which is above 85%.